Of its five acyl carrier proteins, only AcpP1 functions in Ralstonia solanacearum fatty acid synthesis - Yin, Yu; Li, Rui; Liang, Wei-Ting; Zhang, Wen-Bin; Hu, Zhe; Ma, Jin-Cheng; Wang, Hai-Hong (Frontiers in Microbiology, 2022)
The fatty acid synthesis (FAS) pathway is essential for bacterial survival. Acyl carrier proteins (ACPs), donors of acyl moieties, play a central role in FAS and are considered potential targets for the development of antibacterial agents. Ralstonia solanacearum, a primary phytopathogenic bacterium, causes bacterial wilt in more than 200 plant species. The genome of R. solanacearum contains five annotated acp genes, acpP1, acpP2, acpP3, acpP4, and acpP5. In this study, we characterized the five putative ACPs and confirmed that only AcpP1 is involved in FAS and is necessary for the growth of R. solanacearum. We also found that AcpP2 and AcpP4 participate in the polyketide synthesis pathway. Unexpectedly, the disruption of four acp genes (acpP2, acpP3, acpP4, and acpP5) allowed the mutant strain to grow as well as the wild-type strain, but attenuated the bacterium’s pathogenicity in the host plant tomato, suggesting that these four ACPs contribute to the virulence of R. solanacearum through mechanisms other than the FAS pathway.